Ethical aspects for palliative care nursing in intensive care: an integrative review (Research, Society and Development, 2021)
Objectives: Conducting an integrative review of scientific productions on the ethical aspects of palliative care for nursing in intensive care. Methodology: An Integrative Literature Review (ILR), exploratory, qualitative. The choice of ILR occurred in the face of the search for information on the subject, based on studies already published. Results: A total of 1035 articles were identified in the PubMed, Embase, BVS//Lilacs and Cinahl databases. Of these, 73 duplicate articles were eliminated with and without the ICU descriptor, totaling 962 articles. When disregarding the descriptor "intensive care", 849 articles were found and, by including the descriptor "intensive care", 113 articles were found. We considered the articles with complete abstract in English, Portuguese and Spanish with the descriptor ICU, resulting in 113 articles. Of these, 9 were selected. A hundred were excluded, 98 for fleeing its scope and 6 for not presenting a complete abstract, despite the attempt to access the complete manuscript. Conclusion: It is urgent to think and rethink our conducts before the patient and outline strategies for the approach and practice of palliative care in ICU, given the importance of introducing this care so essential since diagnosis. Despite the progress of scientific productions on ethical issues of this care, it is of paramount importance for the theme to be widely discussed among the professionals involved and when they come across the patient in palliative care in intensive care, he may have more assertive conducts and more inclusive-participatory communication of all professionals in decision-making.